2020
DOI: 10.6028/nist.ir.8331
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Face Recognition Vendor Test (FRVT) part 6B :

Abstract: This is the second of a series of reports on the performance of face recognition algorithms on faces occluded by protective face masks [2] commonly worn to reduce inhalation and exhalation of viruses. Inspired by the COVID-19 pandemic response, this is a continuous study being run under the Ongoing Face Recognition Vendor Test (FRVT) executed by the National Institute of Standards and Technology (NIST). In our first report [8], we tested "pre-pandemic" algorithms that were already submitted to FRVT 1:1 prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 1 publication
4
117
0
1
Order By: Relevance
“…We use the synthetic mask generation method described by the NIST report [14]. The synthetic generation method depends on the Dlib toolkit [31] to detect and extract 68 facial landmarks from a face image.…”
Section: Methodsmentioning
confidence: 99%
“…We use the synthetic mask generation method described by the NIST report [14]. The synthetic generation method depends on the Dlib toolkit [31] to detect and extract 68 facial landmarks from a face image.…”
Section: Methodsmentioning
confidence: 99%
“…The NIST [3] recently reviewed the performance of FR algorithms before and after the COVID-19 pandemic. They evaluated the existing algorithms (pre-pandemic) after tuning them to deal with masked or concluded faces.…”
Section: Related Studiesmentioning
confidence: 99%
“…Recently, the National Institute for Standards and Technology (NIST) [3] presented the performance of a set of face recognition algorithms developed and tuned after the COVID-19 pandemic (post-COVID- 19), which follows their first study on pre-COVID-19 algorithms [4]. They concluded that the majority of recognition algorithms evaluated after the pandemic still show a performance degradation when faces are masked.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, concerning AI risk Id, we observe one main failure cluster which is connected to unanticipated post-deployment usage modes and contexts which also includes eventual complications within unusual interactions of the AI system in a dynamically changing environment. Notable examples are failures of facial recognition AI linked to COVID-19 causing the widespread use of facial masks [106][107][108], the invariant responses of natural language processing systems when faced with nonsensical instead of usual meaningful queries [109] (disclosing the low level of understanding) and the AI-based censorship of a picture displaying ancient slavery settings due to a forerunning misclassification labelling the sample as displaying nudity [110]. Other cases include unknown latent biases in medical AI [111] and other forms of biases in medical AI that unfold post-deployment as a function of geographical factors [112].…”
Section: Rda For Ai Risk Instantiations Ic and Id-examplesmentioning
confidence: 99%